Quantum Estimation in Driven-Dissipative Optomechanics: Beyond the Linear Model - Sala, Kamila (2023)
This thesis examines the optimal estimation of parameters in a variety of quantum oscillator models, including cavity quantum optomechanics and the quantum van der Pol oscillator. To achieve this, we employ theoretical tools from open quantum systems, quantum estimation theory and Gaussian states. In all cases, we compare the ultimate limits to parameter estimation (quantum Cramer-Rao bounds) to the performance of experimentally feasible observables (e.g. quadrature or number operator measurements).